Clinical Insights to Complete and Incomplete Surgical Revascularization in Atrial Fibrillation and Multivessel Coronary Disease - Pasierski, Michal; Staromłyński, Jakub; Finke, Janina; Litwinowicz, Radoslaw; Filip, Grzegorz; Kowalówka, Adam; Wańha, Wojciech; Kołodziejczak, Michalina; Piekuś-Słomka, Natalia; Łoś, Andrzej; Stefaniak, Sebastian; Wojakowski, Wojciech; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Although endorsed by international guidelines, complete revascularization (CR) with Coronary Artery Bypass Grafting (CABG) remains underused. In higher-risk patients such as those with preoperative atrial fibrillation (AF), the effects of CR are not well studied. Methods: We analyzed patients' data from the HEIST (HEart surgery In atrial fibrillation and Supraventricular Tachycardia) registry. Between 2006 and 2019 we identified 4,746 patients with pre-operative AF and multivessel coronary artery disease who underwent isolated CABG. We divided the cohort according to the completeness of the revascularization and used propensity score matching (PSM) to minimize differences between baseline characteristics. The primary endpoint was all-cause mortality. Results: Median follow-up was 4.7 years ([IQR 2.3-6.9]). Propensity score matching resulted in 1,009 pairs of complete and incomplete revascularization. Number of distal anastomoses varied, accounting for 3.0 +- 0.6 vs 1.7 +- 0.6 respectively. Although early (<24h) and 30-day postoperative mortalities were not statistically different between non-CR and CR patients (Odds Ratio [OR] and 95% Confidence Intervals [CIs]: 1.34 [0.46-3.86]; P=0.593, Hazard Ratio [HR] and 95% CIs: 0.88 [0.59-1.32]; P=0.542, respectively) the long term mortality was nearly 20% lower in the CR cohort (HR [95%CIs] 0.83 [0.71-0.96]; P=0.011). This benefit was sustained throughout subgroup analyses, yet most accentuated in low-risk patients (younger i.e. <70 y.o., with a EuroSCORE II <2%, non-diabetic) and when off-pump CABG was performed. Conclusions: Complete revascularization in patients with pre-operative AF is safe and associated with improved survival. Particular survival benefit with CR was observed in low-risk patients undergoing off-pump CABG.